Aksiologi Pendidikan Islam dalam Penggunaan Gadget bagi Penghafal Al-Qur’an di Era Digital (Studi Kasus di Pondok Pesantren Tahfidz Al Atsar Yogyakarta) - Mujiburrohman, Mujiburrohman; Muzahid, Hizbullah (TSAQOFAH, 2026)
Developments in digital technology, particularly the use of gadgets, present both challenges and opportunities for Islamic educational institutions, including pesantren tahfidz of Al-Qur’an, because on the one hand they can support learning processes and access to knowledge, while on the other they may generate distractions, weaken the adab of knowledge seekers, and disrupt the quality of Al-Qur’an memorization. This study aimed to examine the use of gadgets among Al-Qur’an memorizers at Pondok Pesantren Tahfidz Al Atsar Yogyakarta from the perspective of the axiology of Islamic education. It employed a qualitative approach with a philosophical-normative paradigm and a case study strategy, with data obtained through interviews with the pesantren leader, ustadz of tahfidz, and santri, observations of student activities, and documentation studies of pesantren regulations. The data were analyzed using thematic analysis within the framework of the axiology of Islamic education, the concept of adab of knowledge seekers, and the principles of maslahah and mafsadah in the use of technology. The findings show that gadgets are understood as neutral tools that acquire value when used in accordance with the educational goals of tahfidz, while gadget restriction policies are based on considerations of public benefit, the preservation of adab, discipline, and the quality of students’ memorization. Controlled gadget use helps maintain learning focus and the quality of Al-Qur’an memorization, whereas unregulated use potentially generates negative impacts. This study underscores the importance of an axiological approach to managing digital technology in Islamic educational institutions so that its utilization remains aligned with the values and objectives of Al-Qur’an memorization education.